Does morphological maturity anticipate physiological maturity? The pattern of sexual maturity in males of the seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) - Andrioli, Guilherme Casemiro [UNESP]; Paschoal, Lucas Rezende Penido [UNESP]; Davanso, Thiago Maia [UNESP]; Costa, Rogério Caetano [UNESP]; Zara, Fernando José [UNESP] (Elsevier, 2024)
The seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) is an important fishing resource and is intensely exploited in South America. Therefore, for the correct and sustainable use of this fishing resource, it is necessary to employ multiple tools to determine the sexual maturity of this species, a key condition for the maintenance of this important economic resource. In this work, we evaluated the morphological (development of secondary sexual characteristics) and physiological (maturation of the reproductive system) sexual maturities in males of X. kroyeri, through the macroscopic and microscopic description of the testes, vasa deferentia and petasma from the juvenile stage to the adult stage. The male reproductive system of seabob shrimp is a paired organ with testes connected to a vasa deferentia, which is anatomically differentiated into three regions: proximal (PVD) (subdivided into anterior, or PVDa, and posterior, or PVDp), medial (MVD) and distal (DVD), the latter region being associated with the terminal ampulla. The morphological maturity of males preceded physiological maturity, meaning the petasma must be formed for the production of seminal fluid and the formation of spermatozoa contained in spermatophores to occur. Petasma formation occurred in the size class 12 ┤13 mm CL, while the production of spermatozoa and spermatophores occurred from 14.1 mm CL. These spermatophores are completely formed in the PVDp and are glycoproteic. Spermatophores are stored in the simple tube of the MVD and DVD. In the DVD, there is an accessory gland forming the ampulla, which produces part of the seminal fluid. The deposition of spermatophores occurs internally in the female's thelycum with the aid of the petasma, which deposits the seminal fluid in the seminal receptacles or spermathecae. At the end of this process, the thelycum is sealed by a secretion from the accessory gland in the male's ampulla, forming a sperm plug. Based on the results obtained here, we recommend that only physiologically mature males of X. kroyeri (> 14.1 mm CL) should be exploited by artisanal fisheries and that macroscopic inspection of the ampulla to determine physiological maturity in this species should be avoided, as this region of the DVD has the accessory gland as its main part, a structure responsible for forming the sperm plug, which does not contain spermatozoa or participate in the formation of spermatophores.
Keywords: Histology; Male reproductive system; Multidisciplinary approach; Penaeidae; SEM